The long arm of the list. (Economist, 2017)
The article discusses the importance of lists in business and changes brought about by technology in the trust business. Topics include the popularity of blockchain technology which allows the system to maintain the list without any external monitoring, the creation of bitcoin with the blockchain database which provides the transaction information independently, and oppositions to distributed ledger possible and decentralization of organizations.